PROBLEMY LINGWISTYCZNEGO OPISU KATEGORII PROTOTYPOWYCH (NA PRZYKŁADZIE KATEGORII POJĘCIOWEJ ROBAK) - Pędzich, Ewelina (Acta Neophilologica, 2017)
This paper presents the Author’s method for describing prototype categories based on dictionary and corpora data. The case of the conceptual category ROBAK demonstrates that prototype theory’s standard and extended versions’ tools (distinguished by Georges Kleiber) are insufficient to reconstruct some conceptual categories. ROBAK is an example of an atypical category both collective and taxonomic. Within the approach presented in this paper the Author attempts to bring together the conceptualization of a prototype as a set of features and cue validity parameter as an indicator of importance of a single feature for the category. The Author proposes a set of steps leading to the reconstruction of the prototype structure of the category ROBAK. Those steps may also be employed to analyze other categories.